Effectiveness of individual and organizational strategies to address workplace bullying - Gardner DH; Bentley T; Catley B; Cooper-Thomas H; O'Driscoll M; Trenberth L (The New Zealand Psychological Society, 2013)
Workplace bullying remains a significant problem in many organisations worldwide, with significant negative impact on the wellbeing of individuals, organisations and communities. Interventions tend to be reactive, addressing individual perpetrators and targets rather than the structural or systemic factors that facilitate bullying. Individual coping responses which directly address the problem, such as counter-attacks or reporting, tend to escalate problems. Effective solutions are most likely to involve organisational factors such as constructive leadership, perceived organisational support and the presence of effective strategies for managing bullying. An organisation-wide survey was completed in New Zealand by 1733 employees from four sectors: healthcare (42%), education (27%), hospitality (8%) and travel (19%). Perceived organisational support, constructive leadership and effectiveness of organisational strategies were expected to be associated with reduced levels of bullying, and to weaken the positive association between bullying and strain and the negative relationship between bullying and wellbeing. In contrast, individual-level task-focused and emotion-focused strategies were expected to be associated with increased levels of bullying and to worsen the effects of bullying on strain and on wellbeing. Direct and moderated effects were analysed and implications for research and practice will be discussed.